An EKG Interpretation Primer - Christianson, Jacqueline; Team, Nurses International; organization, NP-C; organization, MSN; Open Textbook Library (Open Textbook Library, 2019)
This book teaches healthcare professionals the basics of EKG interpretation and is available as a Creative Commons resource.
Chapter 0 - Anatomy and Physiology of the Heart -- Chapter 1 - EKG Basics and Terminology -- Chapter 2 - Electrical Activity of the Heart and Basic Wave Forms on an EKG -- Chapter 3 - EKG Machinery and Setup -- Chapter 4 - Rhythm Interpretation -- Chapter 5 - 12 Leads and Special Rhythms
In English.
Description based on print resource
Keywords: Biology -- Textbooks